Peran Keluarga Orang Tua Kepada Anak Balita Dalam Membentuk Karakter (Studi Pada Orang Tua Pemula) - Habib Al Muzny (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2020)
Abstract: The article with the title 'The Role of Parents' Families To Toddlers in Forming Character (Study of Beginner Parents),' aims to 1) Analyze the patterns of communication that parents make to their children, 2) Analyze the use of verbal and nonverbal communication by parents to toddlers. 3) looking for communication models carried out by parents to toddlers. The method used in this study is a qualitative descriptive approach to in-depth interviews with toddler parents. Conclusion Parent to child communication patterns are influenced by protective patterns with pluralistic patterns as well as the combination of protective patterns with consensual patterns. Parental verbal communication to children in parenting uses words that are easily understood by children, gentle, firm. nonverbal communication of parents to children hugging children when invited to other family homes, invited to go to a place of recreation. Model of family communication from parents between father and mother there are differences in the family communication model of family communication conducted by fathers using protective and laizzer-fair patterns, while the family communication model conducted by mothers uses modification or combination. Keywords: Family role; interpersonal communication. Abstrak: Artikel dengan judul ‘Peran Keluarga Orang Tua Kepada Anak Balita Dalam Membentuk Karakter (Studi Pada Orang Tua Pemula),’ ini bertujuan untuk 1) Menganalisis Pola komunikasi yang dilakukan orang tua kepada anak, 2) Menganalisis penggunaan komunikasi verbal dan nonverbal yang dilakukan orang tua kepada anaka balita. 3) mencari model komunikasi yang dilakukan oleh orang tua kepada balita. Metode yang digunakan pada penelitian ini adalah deskriptif kualitatif dengan pendekatan wawancara mendalam kepada orang tua balita. Kesimpulan Pola komunikasi orangtua kepada anak a dipengaruhi oleh pola protektif dengan pola pluralistik juga gabungan pola protektif dengan pola konsensual, Komunikasi verbal orangtua kepada anak pada pola pengasuhan menggunakan kata yang mudah difahami anak, lemah lembut, tegas. komunikasi nonverbal orangtua kepada anak memeluk anak saat diajak kerumah keluarga lain, diajak jalan ketempat rekreasi. Model komunikasi keluarga dari orangtua antara ayah dan ibu terdapat perbedaan dalam model komunikasi keluarga komunikasi keluarga yang dilakukan oleh ayah lebih mengunakan pola protektif dan laizzer-fair, sedangkan model komunikasi keluarga yang dilakukan oleh ibu lebih mengunakan modifikasi atau gabungan. Kata kunci: Peran keluarga; komunikasi interpersonal.